ANALISA KIMIA KAYU PADA TANAMAN Araucaria cunninghamii Aiton ex D.Don UNTUK BAHAN BAKU PULP - Dedi Setiadi; Mudji Susanto; Mohammad Anis Fauzi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Araucaria cunninghamii is one of the endemic needles tree species grown naturally in Papua. The material used in the study is wood of A.cunninghamii that was planted in the first-generation of progeny test in Bondowoso, East Java. This study aims to determine the characteristic chemical properties of A.cunninghamii wood from some provenances as raw material for pulp. Disk of wood samples were taken from the stem at 50 cm above the ground with 5 cm of thickness. Testing chemical properties include the levels of toluene extractives soluble in ethanol, hot water soluble extractives, holocellulose, cellulose and lignin. Data were analyzed to determine the effect of provenance to chemical properties of wood. The results of study showed that wood sample of A.cunninghamii contained 73.33% holocellulose, 46.39% cellulose, lignin 30.56%, 1.19% ethanol solubility and 1.34% hot water solubility. Based on the composition of chemical substances contained in the wood, A.cunninghamii generally has good quality to be used as raw materials of pulp and paper.